The Role of Reading Art Books to Young Children - Khudoykulova Feruza Maksudjonovna (International Journal on Integrated Education, 2022)
One of the most significant and effective teaching resources is children's literature. Children's books are being published in prodigious amounts right now. Children's books are offered for sale in shops, kiosks, and on open shelves. In this article, the function and significance of reading aloud to kindergarten students are discussed.